Fostering creativity and moral values among preschool children through multimedia storyboards - Suboh, Nadiah; Ibrahim, Rahinah; Yasran, Adi (Human Resource Management Academic Research Society, 2023)
This study found the need to explore the abilities of preschool children in developing creativity and applying moral values while interacting with multimedia storyboards. The study conducted is a case study involving a group of 5 preschool children aged 6 years old in Melaka. The study's findings were processed using a qualitative approach and the NEMD Theory from the generated storylines. The study's results recorded that when children tell stories using multimedia storyboards, the resulting storylines are more complex and incorporate moral values spontaneously compared to storytelling without multimedia storyboards. The findings of this study can fulfill the Student Aspirations in the Education Development Plan (2013-2025), which aims to produce students with communication skills. Furthermore, this study can serve as a guide not only for children but also for maximizing the emergence of talents that can enhance the quality of the country's education.